Impact of Social Media and Peer Pressure on Moral Disengagement among Secondary School Students in Onitsha North LGA, Anambra State - Ojiakor-Umenze, Ifeoma; Nelson Etodike, Chukwuemeka Nelson Etodike; Evelyn Uchechukwu, Nwafor; Alex, Njoku (Universitas Ahmad Dahlan, 2024)
Nigerian students are at a crossroads because of the rapid erosion of the value system in Nigeria, not because of corruption, unemployment, and poverty. The emergence of social media and peer influence has a different impact. This study explored the effects of social media and peer pressure on moral disengagement among secondary school students in Onitsha North LGA of Anambra State. The research sample size was 400 secondary school students selected through a multi-stage sampling technique from a population of 1,400 secondary school students in 12 government secondary schools in the Onitsha Education Zone. The results show that the presence of participants on social media, such as WhatsApp, Facebook, Instagram, etc., is quite high, with more than half of the population 167 (50.9%) always using social media. These findings also reveal the high use of social media among students, which may hurt student life, especially moral life. It was also confirmed that friendship and fun were the main satisfactions students got from social media, with a combined rate of 68% for 238 students. In addition, peer pressure has a negative (but not significant) impact on students' moral disengagement. However, this impact did not reach a substantial proportion at β = 0.06, p > 0.05 (n = 389), which means that the results did not support the first hypothesis, so it was rejected. Social media has a positive and significant impact on students' moral disengagement at β = 0.49, p < 0.05 (n = 389). These findings reveal a directly proportional impact of social media use on students' moral disengagement. It is recommended that parents, teachers, and other guardians regulate internet exposure via social media in teenagers and young adults to prevent them from becoming too busy or becoming addicted.